Acupuncture as an adjunctive therapy for sleep fragmentation in Parkinson’s disease: a pilot study based on polysomnography - Sheng, Jili; Sun, Yingying; Liu, Tao; Zhu, Jianfang; Zhang, Qinhong; Jin, Xiaoqing (Frontiers in Neurology, 2025)
ObjectiveThis pilot study aims to assess the feasibility and preliminary effectiveness. of acupuncture as an adjunct therapy for improving sleep quality in patients with Parkinson’s Disease (PD) who are experiencing fragmented sleep disorders.MethodThis pilot study recruited a small cohort of 11 patients diagnosed. With PD, each undergoing a structured 4-week acupuncture intervention comprising three sessions per week. Outcome measures included polysomnography (PSG) and the Pittsburgh Sleep Quality Index (PSQI), both of which were evaluated at baseline and following the completion of the 4-week acupuncture regimen.ResultPost-intervention analysis showed trends toward improved sleep continuity with statistical significance in the sleep arousal index (p = 0.001), sleep arousal frequency (p = 0.001), and PSQI scores (p = 0.026) compared to baseline measurements. Importantly, no adverse events or complications were reported throughout the study period.ConclusionThe results indicate that acupuncture provides preliminary evidence supporting its use as a feasible adjunctive therapy for improving sleep quality in individuals with PD. Further research is required to evaluate the long-term efficacy of acupuncture and to examine its practicality and feasibility for integration into established PD management protocols.